INFORMATION CULTURE IN THE STRUCTURE OF ADAPTIVE-PRODUCTIVE DEVELOPMENT OF PERSONALITY IN THE SYSTEM OF CONTINUOUS EDUCATION - N. Balitskaya; N. Kozyrev; O. Kozyreva (Вестник Северо-Кавказского федерального университета)
The article defines the possibilities and methodological basis for the formation of information culture of the individual in the system of continuous education in the constructs of adaptive and productive development. Specifics theoretical clarify andjustify opportunities to improve the quality of the adaptive-productive challenges of development in the constructs of information culture of personality in the structure of continuing education presents the definitions, the models, the author's typology of models of information culture of personality in the context of adaptive and productive development of the personality in the system of continuous education. Selected, analyzed, clarified and resolved components theoretical study of the information culture in the context ofadaptive and productive development; presents the components of goal-setting; dedicated, innovative, marked, gnoseological didactically substantiated and disclosed functions, principles, methods and techniques of adaptive-productive development of the personality in the system of continuous education.